Protecting Women from the Negative Effects of Body Dissatisfaction: The Role of Differentiation of Self. Issue 3 (2nd October 2018) - Buser, Juleen K.; Gibson, Sandy
ABSTRACT: Body dissatisfaction is a prevalent and concerning issue among college age women. Due to its strong association with eating pathology, identification of moderating variables is a crucial line of inquiry. The present study investigated the ability for an intrapersonal differentiation-of-self variable ("I" position) to attenuate the impact of body dissatisfaction on anorexia and bulimia symptoms among college women participants. Study findings indicated that an "I" position moderated the body dissatisfaction-bulimia relationship and the body dissatisfaction-anorexia relationship. These findings signified the protective influence of a high "I" position for women with high levels of body dissatisfaction. Research and therapeutic implications are discussed.